A DNA-encoded recipe to direct multistage colloidal assembly - Pepijn G. Moerman; Cheng-Hung Chou; Thomas E. Videbæk; W. Benjamin Rogers; Rebecca Schulman (Proceedings of the National Academy of Sciences, 2026)
In equilibrium self-assembly, microscopic building blocks spontaneously self-organize into stable structures as dictated by their interaction potentials, which limits the accessible structural features to those that correspond to global minima in free energy landscapes; they are often ordered and periodic on length scales comparable to the building block size. Coupling the assembly process to an exergonic reaction drives the system out of equilibrium so that an assembly pathway can be engineered to target a specific kinetically stabilized state, which in principle opens up a vast design space with access to diverse complex structures with features on multiple length scales. However, the question of how such features might be specifically targeted remains unanswered. Here, we explore this design space using a DNA-encoded recipe consisting of multiple biomolecular reactions that dictate the time-dependent binding strength and specificity of each type of subunit in the sample independently, which makes it possible to program an assembly pathway that leads to a kinetically trapped final state. With this kinetic control, we show that the same set of building blocks can form clusters with different final structures. These structures, with tunable core-shell compositions, have feature sizes much larger than the building block size and are governed by the DNA-encoded assembly kinetics. Tuning the timing of individual biomolecular reactions using DNA-encoded recipes offers the opportunity to independently regulate how the many interactions of a large set of coassembling components evolve over time, opening up the potential of creating morphogenesis-like assembly processes involving engineered species.